A presença do exército e da aeronáutica na organização espacial de Santa Maria - RS - Machado, Márcia Kaipers (2008)
The present research show a carefully study about the military presence in the Municipality of Santa Maria, Rio Grande do Sul, since his origens until our days give special importance in the spatial organization of the comunity along the times, as well the military unities here situated in the portuguese and brasizilian geopolitcs during the Colonial, Imperial and Republicans times. The origins of the city of Santa Maria góes back to the diplomatic treaty agreement of Saint Ildefonso, Spain, 1777 and then started a presence militarys unities in the municipality and engagement in the military conflicts of the countries of the Rio of de la Plata that assured a very important Geo-strategicaly presence of Santa Maria in the south of Brazil. For this studies was fetched support in the Teoritical and Methodically based in the geo-historical method, that try to explain the origens and the spacial organization of a specific view in the present with the restrict, conditionals of the historical times that gives a historic and political context that gives origens to the formation of this town. In this view study aproaches the geopolitical, terrtory and borders context. As well the formation of the Rio Grande do Sul in the way to understand the military presence in the geographic space of Santa Maria. The armed forces presence in Santa Maria was due to a geopolitical determination, since its up coming through participation of the defense of the brasilian borders and armed conflitcts wit the neighbourn countries, as example of the Oribe and Rosas wars and the of Paraguay. In this one were engaged the natives of Santa Maria, soldiers of the Seventh Cavalry Infantary Regiment and the Mallets Regiment. Santa Maria is situated in the central área of Rio Grande do Sul state, from these unities the city became a very importnt strategic-military pole, that concentrates a major contigent of the Army ando Air Forces. The establishment of the Army and the Air Force in the city in the present as in the past had a great importance for the spacial building and urban expansion. The military personnel here based gave a big support for the economic life. With the support of the military forces personnel and their families gives forces to the business activity, schools and colleges, social life, hospitals and filantropic societies and medical care services.